1989
DOI: 10.1099/00207713-39-1-35
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Relationships and Taxonomic Localization of Unclassified Pseudomonas and Pseudomonas-Like Strains by Deoxyribonucleic Acid:Ribosomal Ribonucleic Acid Hybridizations

Abstract: The deoxyribonucleic acid (DNA):ribosomal ribonucleic acid (rRNA) hybridization technique was used to reveal the relationships and taxonomic positions of an additional 83 strains belonging to 43 saprophytic or pathogenic Pseudomonus species and 29 named and unnamed Pseudomonus-like strains. The DNA:rRNA hybrids were characterized by the following two parameters: (i) the temperature at which one-half of the hybrid was eluted and (ii) the percentage of rRNA binding (the amount of rRNA bound per 100 pg of filter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(58 citation statements)
references
References 40 publications
2
56
0
Order By: Relevance
“…P, avenae and P. cattleyae were included in section V of the genus Pseudomonas in Bergey's Manual of Systematic Bacteriology (28). The results of rRNA-DNA hybridization experiments performed with P. avenae and P. cattleyae (9,11,55) demonstrated that these bacteria belong in the Pseudomonas acidovorans rRNA complex in rRNA superfamily I11 (11,28). In 1992, Willems et al (54) proposed the transfer of P. avenue and P. cattleyae to the new genus Acidovorax (53) as Acidovorax avenue subsp.…”
Section: P Cepacia P Gladioli ("Pseudomonas Marginata") Pseudomonmentioning
confidence: 99%
See 1 more Smart Citation
“…P, avenae and P. cattleyae were included in section V of the genus Pseudomonas in Bergey's Manual of Systematic Bacteriology (28). The results of rRNA-DNA hybridization experiments performed with P. avenae and P. cattleyae (9,11,55) demonstrated that these bacteria belong in the Pseudomonas acidovorans rRNA complex in rRNA superfamily I11 (11,28). In 1992, Willems et al (54) proposed the transfer of P. avenue and P. cattleyae to the new genus Acidovorax (53) as Acidovorax avenue subsp.…”
Section: P Cepacia P Gladioli ("Pseudomonas Marginata") Pseudomonmentioning
confidence: 99%
“…avenae and Acidovorax avenae subsp. cattleyae had the same chemotaxonomic characteristics and could be distinguished clearly from the genus Pseudomonas sensu strict0 (P. jluorescens rRNA branch [ll]), Burkholderia species, Comamonas species, and Hydrogenophaga species on the basis of phenotypic characteristics (10,17,28,35,38,44), ubiquinone systems, DNA base compositions, DNA-DNA homology data, and rRNA-DNA hybridization data (9,11,52,53) (Table 9). Minimal characteristics for differentiating the genera Burkholderia, Acidovorax, Comamonas, Hydrogenophaga, and Pseudomonas are shown in Table 9.…”
Section: + + + --+ + -+ + -+ + --+ + -mentioning
confidence: 99%
“…A striking similarity of 95 % was found between the Xylella fastidiosa 16S rDNA sequence and that of Pseudomonas boreopolis, a bacterium isolated from the soil. There is, however, some uncertainty about the taxonomic position of P. boreopolis, which could be assigned to the genus Xanthomonas on the basis of DNA-rDNA hybridization (De Vos et al, 1989). The similarity levels between Xanthomonas species and Xylella fastidiosa strains ranged from 94n3 to 96n1% and the highest similarity value was found between Xanthomonas campestris and strain PE.PLS.…”
Section: Comparison Of the 16s Rdna Sequencesmentioning
confidence: 99%
“…(Tchan & New, 1984) and the group I fluorescent Pseudomonas spp. (De Smedt et al, 1980;De Vos et al, 1989), also produces an extracellular fluorescent compound when cells are cultured under ironlimited conditions (Johnstone, 1957 ;Thompson & Skerman, 1979). Although D. B. Johnstone and co-workers first suggested similarities between the fluorescent compounds elaborated by A .…”
Section: Introductionmentioning
confidence: 99%